Leadership Styles in Healthcare Settings and Their Impact on Clinical Outcomes: A Systematic Review and Meta-Analysis - Amir Hamzah; Wahyudi Wahyudi; Isa Harpika Br Ginting (Pusat Riset dan Inovasi Nasional, 2026)
Effective leadership in healthcare settings has been increasingly recognized as a critical determinant of clinical outcomes and organizational performance. This systematic review and meta-analysis examines the relationship between various leadership styles and clinical outcomes in healthcare settings. To synthesize evidence regarding the impact of different leadership styles on clinical outcomes, including patient mortality, safety, satisfaction, and quality of care in healthcare settings. Methods: A comprehensive systematic review was conducted following PRISMA guidelines. Electronic databases including PubMed, Scopus, Web of Science, CINAHL, and Embase were searched for peer-reviewed studies published between 2023 and 2024. Studies examining the relationship between leadership styles and clinical outcomes in healthcare settings were included. Data extraction, quality assessment, and meta-analysis were performed according to standardized protocols. The review identified transformational leadership as the most extensively studied and effective leadership style in healthcare settings. Evidence demonstrates significant positive associations between transformational leadership and improved clinical outcomes, including reduced patient mortality, enhanced patient safety, and increased patient satisfaction. Servant leadership, transactional leadership, and adaptive leadership also showed positive correlations with various clinical outcomes. The pooled effectiveness of leadership interventions was 14.0% in before-after studies, with a correlation coefficient of 0.22 in cross-sectional studies. Leadership styles, particularly transformational and servant leadership, significantly impact clinical outcomes in healthcare settings. Healthcare organizations should prioritize leadership development programs and tailor leadership approaches to specific contexts to enhance patient care and organizational performance.